Case-control study for assessment of factors associated with periodontitis among adults attending university hospital in Karachi, Pakistan - Sara Rafique; Sadaf Khan; Shahbaz Ahmed; Masood Anwar Qureshi; Rafat Amin (Journal of the Pakistan Medical Association, 2020)
Objective: To compare the physiological and biochemical markers in healthy and periodontitis subjects, and to relate these markers with the periodontal health condition. Methods: The case-control study was conducted at the Dow University of Health Sciences, Karachi, from April 2017 to March 2018, and comprised systematically healthy controls and periodontitis cases. Periodontal probing depth, clinical attachment loss, oral hygiene indices, educational status and body mass index were recorded for all the subjects. Serum levels of biochemical markers, including calcium, phosphate and interleukin-6, were also measured. Data was analysed using SPSS 16. Results: Of the 150 subjects, 75(50%) each were in the case and control groups. The overall mean age was 31.23+3.7 years (range: 22-42 years). The cases had relatively poor oral hygiene indices and educational status compared to the controls (p<0.05). Serum calcium level was lower, whereas mean body mass index was higher in the cases compared to the controls (p<0.05). No significant difference was found in interleukin-6 and phosphate levels (p>0.05). Clinical attachment loss showed significant correlation (p<0.05). Conclusion: Low serum calcium and educational levels, higher body mass index and poor oral hygiene were found to be the risk factors for the progression of periodontitis. Key Words: Periodontitis, Serum calcium, BMI, Oral hygiene, Clinical attachment loss. Continuous...